An Examination of Shareholders Wealth Effects of Mergers and Acquisitions in Short Term: The Evidences from U.S. Public Target Acquisitions - Han, Jin (2011)
This paper examines the shareholders wealth effects in short run of U.S. domestic public target acquirers using alternative payment methods from 2001 to 2005, providing insights into what can learn from the stock abnormal returns to public target acquirers when they announcing an acquisition. At a first level the study documents that, in short run, public target acquirers significantly lose value. This result is robust after controlling for acquirer firm size (large/small) and bidder’s book-to-market ratio (value/glamour). Secondly, the study further investigates the variation in announcement returns to acquirers by isolating the market’s perception of various characteristics of deal, target and acquirer, including acquirers’ firm size, target relative size, payment methods, industry diversification, acquirer’s book-to-market ratio and target Tobin’s Q ratio. Importantly, the results indicate the cash financed acquirers obtain a significantly superior abnormal return than stock financed acquirers by 3.17% when purchasing public target, while this sort of finding is reinforced after taking acquirer firm size, core-industry(diversified/non-diversified) and bidder’s book-to-market ratio into account. In addition, the study further claims that the acquirers’ abnormal returns are negatively related to acquirer firm size, target relative size and target Q ratio, whereas are positively related to bidder’s book-to-market ratio. Nonetheless, the OLS regression suggests that within these factors, cash payment and bidder’s book-to-market ratio are not significantly related to bidders’ abnormal returns in short run.